Embedding assessment in learning experiences: enacting the principles of instructional alignment in physical education teacher education. Issue 1 (2nd January 2023) - Scanlon, Dylan; MacPhail, Ann; Walsh, Claire; Tannehill, Deborah
ABSTRACT: Appreciating that a significant amount of assessment-related literature has focused on the 'what' of assessment (i.e. what to assess), 'the systematic use of assessment to improve learning remains the exception rather than the rule' [Wiliam, D. (2018). Assessment for learning: Meeting the challenge of implementation. Assessment in Education: Principles, Policy & Practice, 25(6), 682–685]. This paper focuses on interrogating 'why' and 'how' assessment can be effectively embedded in the delivery of learning experiences. That is, assessment as a means to engage students in the learning process rather than as an add-on to the learning experience. Instructional (and constructivist) alignment provides a context to embedding assessment before introducing specific developments in physical education teacher education (PETE) that allow us to share implementation of assessment considerations, planning for embedded assessment and embedding assessment as a component of a PETE programme. Worked examples of embedding assessment are provided to convey what embedded assessment involves and looks like. Lessons learned from advocating for the practice of embedding assessment are shared.